PERAN PUBLIC RELATIONS DALAM MEMPENGARUHI KONTEN MEDIA - Hidayat, Rizki (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractIn this era of globalization of business competition is getting higher. Especially in economic sectors where big companies from abroad increasingly free to operate and market its products in Indonesia so that local companies can not compete with itself would be eliminated. The purpose of this study was look at the effectiveness of IT utilization is also the creativity of a public relations. Popularity of media and social networks such as Facebook, Twitter, YouTube, spur the growth of